2D Mechanical Metamaterials with Widely Tunable Unusual Modes of Thermal Expansion. Issue 48 (9th October 2019) - Ni, Xiaoyue; Guo, Xiaogang; Li, Jiahong; Huang, Yonggang; Zhang, Yihui; Rogers, John A.
Abstract: Most natural materials expand uniformly in all directions upon heating. Artificial, engineered systems offer opportunities to tune thermal expansion properties in interesting ways. Previous reports exploit diverse design principles and fabrication techniques to achieve a negative or ultralow coefficient of thermal expansion, but very few demonstrate tunability over different behaviors. This work presents a collection of 2D material structures that exploit bimaterial serpentine lattices with micrometer feature sizes as the basis of a mechanical metamaterials system capable of supporting positive/negative, isotropic/anisotropic, and homogeneous/heterogeneous thermal expansion properties, with additional features in unusual shearing, bending, and gradient modes of thermal expansion. Control over the thermal expansion tensor achieved in this way provides a continuum‐mechanics platform for advanced strain‐field engineering, including examples of 2D metamaterials that transform into 3D surfaces upon heating. Integrated electrical and optical sources of thermal actuation provide capabilities for reversible shape reconfiguration with response times of less than 1 s, as the basis of dynamically responsive metamaterials. Abstract : Design and fabrication of 2D bimaterial serpentine polymer microlattices introduce widely tunable, unusual thermal expansion behaviors. The metamaterials approach to control over the thermal expansion tensor establishes a continuum‐mechanics platform for advanced strain‐field engineering. Incorporating electrical or optical sources of thermal actuation yields controlled modes of switching with response times of less than 1 s.